TRAVEL PATTERN WISATA RELIGI GEREJA DI JAKARTA - Alfredo Mikhael Immanuel; Yudhiet Fajar Dewantara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research originates from the phenomenon of the limited presence of structured travel patterns in church-based religious tourism in Jakarta, as well as the tendency of tourists to visit only the most popular churches. The purpose of this study is to identify the potential of religious tourism through the three main components of tourism: attractions, amenities, and accessibility, and to develop an effective and engaging travel pattern. This study uses a qualitative approach with methods including field observations, in-depth interviews with church visitors and administrators, and visual documentation. Five historic churches were selected as the objects of study: Tugu Church, Pniel Church, Immanuel Church, Sion Church, and the Jakarta Cathedral. The results show that each church possesses a unique appeal in terms of historical value, architectural features, and spirituality. In terms of amenities and accessibility, there are significant differences between locations, which affect the travel patterns of visitors. Three main travel patterns were identified: single point, stop over, and complex neighbourhood. The study concludes that a systematically designed travel pattern can improve the quality of the tourism experience and broaden the distribution of visitor flows. The researcher suggests that the government and church administrators develop integrated religious tourism packages and involve local communities in tourism management.